Fabrication and Evaluation of Mini Tablet Filled Capsules to Treat Transient Ischemic Attack - Thirumalesh Naik, S.B.; Purushothaman, M.; Chandrasekhar, K.B. (Asian Journal of Chemistry, 2020)
In this work, mini tablets filled hard gelatin capsules were fabricated for a fixed-dose therapy for transient ischemic attack (TIA). Clopidogrel besylate (CB)-75 mg and acetyl salicylic acid (ASA)-75 mg were utilized in this work. Among the mini-tablets (MTs) clopidogrel besylate, was uncoated conventional mini-tablets, whereas acetyl salicylic acid was enteric-coated. Acetyl salicylic acid gastric irritation was overcome by using Plantago ovata seed mucilage as a binder in all mini-tablets. Both types of mini-tablets were filled in hard gelatin capsules. Clopidogrel besylate and acetyl salicylic acid compatibility with excipients used were evaluated, all the mini-tablets were judged for post-compression constraints. The prepared mini-tablets confirmed no interaction by FTIR and DSC studies. All the mini-tablets passed the physico-chemical constraints. Clopidogrel besylate was released from the dosage form within 45 min, whereas enteric-coated acetyl salicylic acid mini-tablets resist to release in an acidic environment and released within 45 min in an alkaline buffer. Even the filled capsules were also passed all the parameters evaluated. The study concludes that by using P. ovata as a binder in making tablets will resolve the issues related to gastric irritation.